Notes on Aulaconotus Thomson, 1864 from China, with description of one new species (Coleoptera: Cerambycidae: Lamiinae: Agapanthiini) - Bi, Wen-Xuan; Zhao, Ming-Shui; Lin, Mei-Ying (Zootaxa, 2024)
The male of the little-known species Aulaconotus incorrugatus Gressitt, 1939 is reported for the first time, and its male genitalia compared with the most similar congener, A. semiaulaconotus (Hayashi, 1974). A few new provincial records for A. incorrugatus are given. A new species closely related to the above taxa, A. yangi Bi & Lin sp. nov., is described from southeastern China. Illustrations of the habitus and major diagnostic characters, including endophallic structure, of these three species are provided.